태국 의료관광 수요 결정요인에 대한 탐색적 연구 - 정연국(Yeon-Kook Jeong); 한은진(Eun-Jin Han) (무역연구, 2025)
Purpose – The purpose of this study focused on medical tourism consumers in Bangkok, Thailand, is to provide information on medical tourism consumption promotion sales strategies for the demand market of Thai medical tourism consumers. Design/Methodology/Approach – This study targeted Thai individuals with medical tourism experience, focusing on hospitals in Bangkok, Thailand. The approach of this study is Thai medical tourism selection attribute factor analysis, and the factors influencing each independent variable were analyzed using a truncated Poisson model. The dependent variable is an analysis by applying the number of participations per year. Findings – The estimation results of the determinants of demand for medical tourism in Thailand are as follows. In the analysis result of the medical tourism TP model, it was found that job factors (public officials, faculty and staff, professional, and office workers) have a positive effect on socioeconomic characteristics. The result of analyzing the attribute factors of medical tourism selection shows that advanced medical equipment and procedure waiting time, distance and recreation facilities, product promotion, and various services had a positive effect. Research Implications – The estimated results of this study predict that it will be possible to provide a direction to increase the demand effect of the Thai medical tourism industry in the future. KCI Citation Count: 0